CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE IN HIGH-RISK INDUSTRIES: THE ROLE OF STANDALONE REPORTS AND FIRM CHARACTERISTICS - Hidayat, Muhammad Fahrurrozi; Amalia, Dewi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The issue of Corporate Social Responsibility Disclosure (CSRD) remains a concern in Indonesia, particularly in response to various environmental pollution incidents involving companies. This study aims to examine the influence of profitability, standalone report, firm size, the tenure of the board of directors, the size of the board of commissioners, the proportion of independent commissioners, and managerial ownership on CSRD in energy sector companies. The data were collected using a purposive sampling method, sourced from financial reports and/or sustainability reports published by the companies. The results of the panel data regression analysis indicate that the standalone reports and firm size have a positive effect on CSRD. The variables of profitability, tenure of the board of directors, size of the board of commissioners, independent commissioners, and managerial ownership do not have a significant effect on CSRD. Firm size and standalone report influence CSRD, in line with stakeholder and agency theoretical frameworks.